The contribution of Uthman bin Foduye (d.1817) in changing Nigerian society: A discussion from the perspective of Ibn Khaldun’s concept of Umran / Shuaibu Umar Gokaru - Shuaibu Umar, Gokaru (2017)
Nigeria is one of the most populous countries in Africa and is majority Muslim. Thus, various scholars had attempted to change Nigerian society. Among them was Uthman bin Foduye, who lived from 1754-1817 and contributed toward changing Nigeria to a united society according to the dictates of the SharÊÑah. This is a historical-comparative research analysing the contribution of Uthman bin Foduye in changing Nigerian society from the perspective of Ibn Khaldun’s concept of ÑUmrÉn. The study relies on the books written by Uthman bin Foduye to understand the extent of his thought on societal change. Meanwhile, some key important academics in Nigeria were interviewed to supplement the documentary data to understand the real picture of Uthman bin Foduye’s contribution in Nigeria. The findings reveal that Uthman bin Foduye made evolutionary and revolutionary contributions. His evolutionary contributions comprised peaceful teaching, preaching and writing. Uthman and his community resorted to - due to the plot made by the rulers of Hausaland to assassinate him and his followers. He succeeded in overthrowing their government and establishing his Islamic government known as the Sokoto Caliphate, in present-day, Northern part of the Federal Republic of Nigeria, which its impacts still exist to this day. Ibn Khaldun’s concept of ÑUmrÉn is relevant as both scholars shared the belief that corruption, injustice, imposing a heavy tax on the subjects, indulgence in a life of luxury and favouritism are among the negative factors responsible for the decline of states/societies and dynasties. Moreover, an analysis of Uthman’s writings reveals that Ibn Khaldun’s thought indeed influenced his societal change.